Coprevalence of parasitic infections and diabetes in Sub-Himalayan region of Northern India - Moudgil, Vaishali; Rana, Reetima; Tripathi, Praveen Kumar; Farooq, Umar; Sehgal, Rakesh; Khan, Mohammed Azhar (International Journal of Health Sciences, 2018)
Objectives: Parasitic infections such as toxoplasmosis, hydatidosis, and cysticercosis infect a large population worldwide. Toxoplasma gondii in the pancreas could damage the pancreatic cells. Hence, insulin secretion would be affected which leads to increased risk of diabetes. The present study was designed to investigate the cooccurrence of parasitic infections in patients with diabetes. Methods: A total of 256 confirmed parasitic serum samples were included in the study, of which 95 were positive for toxoplasmosis, 87 for hydatidosis, and 74 for cysticercosis infection. These samples were then analyzed for hyperglycemia. Results: In case of hydatidosis, the frequency of hyperglycemia was 14.94%, followed by cysticercosis (10.8%) and toxoplasmosis (8.42%). The frequency of insulin resistance was analyzed in these hyperglycemic samples. The coprevalence of diabetes was higher in case of hyperglycemic hydatidosis patient samples (11.49%), followed by cysticercosis (8.10%) while the coprevalence of diabetes was minimum (6.31%) in toxoplasmosis patients samples. Thus, the overall prevalence of diabetes with parasitic infections was 8.6%. Conclusion: The study suggested the coexistence of hyperglycemia in hydatidosis, cysticercosis, and toxoplasmosis infected samples. However, higher prevalence of high glucose level was detected among hydatidosis infected samples. Thus, suggested individuals infected with hydatidosis were more susceptible for diabetes in comparison to toxoplasmosis and cysticercosis.